2022
DOI: 10.3390/ma15041483
|View full text |Cite
|
Sign up to set email alerts
|

Study on Delamination Damage of CFRP Laminates Based on Acoustic Emission and Micro Visualization

Abstract: This study investigated the mechanism of delamination damage in the double cantilever beam (DCB) standard test by the use of the strain energy release rate. The curve of the strain energy release rate was verified by the Rise Angle (RA) method. For this purpose, 24-layer carbon fiber/epoxy multidirectional laminates with interface orientations of 0°, 30°, 45°, and 60° were fabricated according to the standard ASTM D5528(13). In the course of this test, acoustic emission (AE) was used for real-time monitoring, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Oftentimes, two or more failure modes can develop together, leading to failure complexity or unpredictability. In most research work, fiber breakage, matrix cracking, and delamination have been studied as the main damage mechanisms [5,[53][54][55]. The main objective of this paper is to apply a deep learning method for the damage classification of composite materials.…”
Section: Materials Preparation and Test Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Oftentimes, two or more failure modes can develop together, leading to failure complexity or unpredictability. In most research work, fiber breakage, matrix cracking, and delamination have been studied as the main damage mechanisms [5,[53][54][55]. The main objective of this paper is to apply a deep learning method for the damage classification of composite materials.…”
Section: Materials Preparation and Test Proceduresmentioning
confidence: 99%
“…During the test, observation and recording of the damage pattern, loading curve and experimental phenomena during the specimen failure were carried out. In order to control the bending stiffness of the thin plate to within a certain range, the combined effects of bending and torsion coupling, cantilever stiffness, and thermal residual stress were considered [5,59]. The delamination test specimen was selected from the carbon fiber composite laminate with the model number T700, and the laying mode of laminate was [0 • ] 24 and had the dimensions 175 mm × 25 mm × 4 mm.…”
Section: Materials Preparation and Test Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…A non-destructive testing method called Acoustic Emission (AE) can be used to identify the beginning and progression of delamination in sandwich structures [1,14]. AE entails monitoring the sandwich structure's high-frequency acoustic waves while it is stressed or deformed.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that matrix cracking resulted in higher frequency values whereas delamination resulted in lower frequency values. Li et al [19] utilised two AE sensors to investigate the influence of delamination length in composite cantilever beam on rise angle and strain energy release rate of the waveforms. The results showed that both parameters can be effectively used in delamination detection.…”
Section: Introductionmentioning
confidence: 99%